2008
DOI: 10.1055/s-2008-1061504
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome in Isolated Single Umbilical Artery

Abstract: Our objective was to determine whether the rate of small for gestational age (SGA) infants and adverse perinatal outcome are increased in pregnancies diagnosed with an isolated single umbilical artery (SUA). We compared 297 pregnancies with a SUA diagnosed on routine obstetrical ultrasound with 297 pregnancies with a three-vessel cord control. Pregnancies complicated by major fetal anomalies were excluded. The rate of SGA, fetal death, and neonatal outcomes were compared between the two groups. Data analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 7 publications
2
47
2
10
Order By: Relevance
“…3 Although several studies have reported diminished fetal growth in these pregnancies, [4][5][6][7][8][9][10][11][12] others have not shown differences. [13][14][15] These contradictory findings may be attributed to diverse methodological differences in the published literature.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…3 Although several studies have reported diminished fetal growth in these pregnancies, [4][5][6][7][8][9][10][11][12] others have not shown differences. [13][14][15] These contradictory findings may be attributed to diverse methodological differences in the published literature.…”
Section: Introductionmentioning
confidence: 66%
“…Eleven series are based on cases diagnosed prenatally and significant differences in birth weight were demonstrated in four out of six studies that included control groups. 6,7,11,[13][14][15]18,[20][21][22][23] On the other hand, all post-natal studies have shown that birth weight is significantly lower in ISUA pregnancies compared to control pregnancies. 5,9,10,12 This is possibly related to the fact that these are the studies with greater sample size.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite these associations, controversy exists regarding the clinical significance of SUA as an isolated finding in a low-risk patient population. Some of the current literature did not demonstrate an increased risk of IUGR in anatomically normal fetuses with SUA and the authors suggested that the remaining artery in SUA fetuses carries twice the blood volume of an artery in a 3VC [4,8,9]. Other studies reported that the finding of SUA is associated with increased incidence of fetal growth restriction, prematurity and perinatal mortality and recommended serial sonograms for fetal growth and close obstetric follow-up [3,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…Esta concordancia demuestra, una vez más, la importancia que la RCIU tiene como factor de riesgo para malformaciones congénitas estructurales, aneuploidías y aberraciones cromosómicas. Gran importancia también tiene el hecho de el alto porcentaje de prematuros en nuestra muestra (55,4%), aún cuando otros autores no encuentran diferencias en la prematuridad entre los niños con AUU y los normales (15). Nuestros hallazgos, sin embargo, están plenamente de acuerdo con lo reportado por otros autores (7).…”
Section: Discussionunclassified